2021
DOI: 10.3389/fped.2021.619738
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Characteristics of COVID-19 Infection in Children

Abstract: SARS-CoV-2, a member of the family coronaviridae, has triggered a lethal pandemic termed coronavirus disease 2019 (COVID-19). Pediatric patients, mainly from families with a cluster of infection or a history of exposure to epidemic areas, get infected via direct contacts or air-borne droplets. Children (aged below 18 years) are susceptible to COVID-19, with an average incubation period of about 6.5 days. Most cases present asymptomatic or common cold symptoms such as fever, cough, and myalgia or fatigue, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 81 publications
2
24
0
4
Order By: Relevance
“…As reported in the literature, a large proportion of children (50.9%) had asymptomatic COVID-19 infection. [11] In India, sero-prevalence among children and younger age group were estimated as a part of a larger nationwide survey on adult age group. The second nationwide sero-prevalence study done in August-September 2020 had reported 9.0% seropositive among 3,021 children aged 10-17 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported in the literature, a large proportion of children (50.9%) had asymptomatic COVID-19 infection. [11] In India, sero-prevalence among children and younger age group were estimated as a part of a larger nationwide survey on adult age group. The second nationwide sero-prevalence study done in August-September 2020 had reported 9.0% seropositive among 3,021 children aged 10-17 years.…”
Section: Resultsmentioning
confidence: 99%
“…As reported in the literature, a large proportion of children (50.9%) had asymptomatic COVID-19 infection. [11]…”
Section: Discussionmentioning
confidence: 99%
“…It is known that immune processes occurring in childhood and old age differ significantly from each other. Children most often carry the illness in an asymptomatic form or as a respiratory infection (common cold) with nonspecific symptoms, such as fever, cough, myalgia, or fatigue [ 36 , 37 ]. In most cases, the illness is milder than in adults and most often it resolves well.…”
Section: Methodsmentioning
confidence: 99%
“…The novel coronavirus affects males and females equally as well as all pediatric age groups; however, it seems that the younger age groups are more symptomatic [ 13 ]. The results of this study show a bimodal age presentation of the patients that presented to the International Medical Center, mainly between 1-3 years and 5-10 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the findings of this study, lymphocytosis and leukocytosis were found to be evident among children with COVID-19 [ 16 ]. Serum inflammatory markers such as CRP were elevated in several studies [ 11 , 13 , 16 ]. Locally in Saudi Arabia, the study conducted by Al Harbi et al in the Western region found eosinopenia to be the most prevalent among their patient population.…”
Section: Discussionmentioning
confidence: 99%